Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780190265076.003.0003
|View full text |Cite
|
Sign up to set email alerts
|

Migration and “Skipped Generation” Households in Thailand

Abstract: Many working-age adults in developing countries leave their homes for jobs to support their families and leave their children behind in the care of their own parents. This chapter focuses on these “skipped generation” households, in which grandparents live only with their grandchildren due to the migration of their adult children. The authors explore the experiences of caregivers, including how tasks and responsibilities are distributed within families, the nature of exchanges between grandparents and their ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A third reason affecting grandparental worries about safety was grandchildren’s access to cell phones. This finding is important because previous research has found that cell phones can enhance family contact and closeness (Ingersoll-Dayton, Punpuing, Tangchonlatip, & Yakas, 2018a; Knodel et al, 2010). However, as noted by our Thai grandparents, cell phones can also provide a false sense of security because grandparents are not certain about their grandchildren’s location.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…A third reason affecting grandparental worries about safety was grandchildren’s access to cell phones. This finding is important because previous research has found that cell phones can enhance family contact and closeness (Ingersoll-Dayton, Punpuing, Tangchonlatip, & Yakas, 2018a; Knodel et al, 2010). However, as noted by our Thai grandparents, cell phones can also provide a false sense of security because grandparents are not certain about their grandchildren’s location.…”
Section: Resultsmentioning
confidence: 75%
“…Grandparents who have primary caregiving responsibility for their grandchildren experience a wide variety of emotions. Caring for grandchildren can be not only enjoyable (Ingersoll-Dayton et al, 2018a) but also evokes considerable worry. The present study expands on previous research by focusing on grandparents’ worries in the context of migration and by broadening the perspective to a non-Western country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases add to the existing literature on intergenerational conflict by highlighting an additional source of family tension in skipped generation families: Grandparents may enjoy providing care for their grandchildren, welcome their company, and appreciate their help (Ingersoll-Dayton, Punpuing, et al., 2018; Ingersoll-Dayton, Tangchonlatip, et al., 2018). Therefore, when their adult children ask the grandparents to give up their grandchildren, a dispute may result.…”
Section: Resultsmentioning
confidence: 84%
“…On the one hand, grandparents may derive a sense of purpose from caring for their grandchildren, appreciate their grandchildren’s companionship, and anticipate the potential for more remittances from their adult migrant children (Baker & Silverstein, 2012; Ingersoll-Dayton, Punpuing, Tangchonlatip, & Yakas, 2018; Ingersoll-Dayton, Tangchonlatip, Punpuing, & Yakas, 2018; Ingersoll-Dayton, Punpuing, Tangchonlatip, & Yakas, 2017; Narongchai & Ayuwat, 2011; Thang, 2012). On the other hand, grandparents may feel trapped by their caregiving responsibilities, worried about their own health, and concerned that they do not have sufficient financial resources to raise their grandchildren (Ingersoll-Dayton, Punpuing, et al., 2018). Another dynamic that can contribute to grandparents’ mixed feelings about caring for grandchildren is intergenerational conflict.…”
Section: Introductionmentioning
confidence: 99%